Evaluating raveling susceptibility of asphalt by Pull-off tests. (18th January 2023) - Beltzung, Françoise; Raab, Christiane; Partl, Manfred N.
Highlights: Development of method to detect raveling of porous pavements. Comparison with other method from European standard. Laboratory and in situ testing. Methods able to detect insufficient compaction. Abstract: Porous low noise wearing courses are popular in Switzerland. However, after 4 to 5 years in service distresses appear mostly due to raveling. Measuring the susceptibility to loss of aggregates is therefore considered a desirable step of quality control. The research project was able to demonstrate the problematic nature of the scuffing test according to EN 12697–50. Instead, it has been shown that a simple pull-off test has many advantages. The handheld device is easy to operate and applicable on site. The method discriminates between types of mix-designs, degrees of compaction and is performing satisfactory with respect to accuracy. It was found that pull-off results correlated reasonably well with visual raveling field inspection.